'Fiasco prime ministers': leaders' beliefs and personality traits as possible causes for policy fiascos. Issue 5 (27th May 2016) - Brummer, Klaus
ABSTRACT: Against the predominantly structural explanations of policy fiascos in the public policy literature, this contribution questions whether idiosyncrasies of individual decision-makers should be considered as alternative sources of foreign policy fiascos. The contribution uses the leadership trait approach and the operational code approach from the field of foreign policy analysis (FPA) to discern the personality traits and political beliefs respectively of British prime ministers who ended up with major foreign policy fiascos. The computer-aided content analysis of more than 900 speech acts shows that British 'fiasco prime ministers' do indeed exhibit certain 'extreme' personality traits (e.g., a considerably higher level of self-confidence) and political beliefs (e.g., a greater inclination to pursue conflictual strategies) that distinguish them from British 'non-fiasco prime ministers' and other world leaders. This suggests that the public policy literature might benefit from allowing for a greater role of individual decision-makers in their analyses of policy fiascos.